Speciation and antifungal susceptibility testing of candida species isolated from clinical samples - Singh, Lokjan; Harakuni, Sheetal U; Basnet, Bibek; Parajuli, Keshab (Asian Journal of Medical Sciences, 2020)
Background: The importance of epidemiological monitoring of yeasts involved in pathogenic processes is unquestionable due to the increase in trend of infections caused by various species of Candida over the last decade; so are the changes observed in species causing Candidiasis and empirical antifungal treatment. Aims and Objective: To speciate the clinically isolated Candida species by phenotypic methods and to estimate the antifungal susceptibility of the isolated species against fluconazole, ketoconazole, voriconazole, itraconazole by disc diffusion method. Materials and Methods: A cross-sectional study conducted in 2018 in the Department of Microbiology, J. N. Medical College, KAHER, Belagavi Karnataka. Ethical Clarence was obtained from institutional ethical committee J.N. Medical College. Results: Out of 59 Candida isolates, Candida tropicalis was the predominant species 41(69.49%), followed by Candida glabrata 5 (8.47%), Candida parapsilosis and Candida lusitaniae 4 (6.78%) respectively, Candida guilliermondii and Candida kefyr 2 (3.39%) respectively and the least one was Candida krusei 1 (1.69%). Voriconazole showed the highest level of sensitivity whereas Itraconazole has shown the least sensitivity pattern by disk diffusion method. Out of 59 Candida species, 52 (88.13%) were sensitive to Voriconazole, 44 (74.57%) were sensitive to Fluconazole, 40 (67.79%) were sensitive to Ketoconazole and the least sensitivity was shown by Itraconazole 30 (50.84%). Candida krusei and Candida guilliermondii showed 100% sensitive to Fluconazole, Voriconazole, Ketoconazole and Itraconazole respectively. Conclusion: Non-albicans Candida species are being common isolates from cases of candidiasis. Candida tropicalis is the predominant isolate, followed by Candida glabrata, Candida lusitaniae, Candida parapsilosis, Candida guilliermondii, Candida kefyr and Candida krusei. Most of the isolates were sensitive to Voriconazole.